Arthrographic Study of the Communication between the Tarsal Joints in Crioulo Horses - Gehm, Marcelo; Duarte, Claudia A.; Leite, Carla T. [UNESP]; Goss, Georgia C.; Dowich, Gabriela; Pereira, Elton P.; Rosa, Loreane R. da; Romero, Bruno G. (Georg Thieme Verlag Kg, 2019)
Objective The aim of the present study is to assess an arthrographic technique based on the access to the equine tarsus via distal intertarsal and on the existence and frequency of communication between distal and tarsocrural joints in the tarsus of Crioulo horses. Materials and Methods Fifty Crioulo horses of both sexes from 3 to 8 years old were included in the experiment. Animals with radiographic signs of tarsal osteoarthritis and joint space loss were excluded from the experiment. Contrast was injected in the distal intertarsal joint and radiographs were taken at two different times - Time 0 (after contrast application) and Time 1 (45 seconds after) to detect any communication between tarsal joints. The recorded results were analysed through chi-squared test. Results Thirty out of three hundred tarsi were excluded from the experiment since the radiographic images showed loss of the distal intertarsal joint space. Positive contrast was injected in distal intertarsal joint of 70/100 tarsi. There was not any contrast overflow in the 30/70 assessed tarsi. Contrast diffused to the tarsometatarsal joint in 32/70 of the assessed tarsi and reached tarsocrural joints in 8/70 tarsi. The adopted arthrographic technique was effective in data collection and evaluation; however, 52/70 of tarsi showed contrast overflow to the bursa of the cunean tendon.
Keywords: horse; arthrography; tarsal joints; treatment; Crioulo horses